A Perspective on Implementation of Technology-Driven Exergames for Adults as Telerehabilitation Services - Meulenberg, Cécil J. W.; de Bruin, Eling D.; Marusic, Uros (Frontiers in Psychology, 2022)
A major concern of public health authorities is to also encourage adults to be exposed to enriched environments (sensory and cognitive-motor activity) during the pandemic lockdown, as was recently the case worldwide during the COVID-19 outbreak. Games for adults that require physical activity, known as exergames, offer opportunities here. In particular, the output of the gaming industry nowadays offers computer games with extended reality (XR) which combines real and virtual environments and refers to human-machine interactions generated by computers and wearable technologies. For example, playing the game in front of a computer screen while standing or walking on a force plate or treadmill allows the user to react to certain infrastructural changes and obstacles within the virtual environment. Recent developments, optimization, and minimizations in wearable technology have produced wireless headsets and sensors that allow for unrestricted whole-body movement. This makes the virtual experience more immersive and provides the opportunity for greater engagement than traditional exercise. Currently, XR serves as an umbrella term for current immersive technologies as well as future realities that enhance the experience with features that produce new controllable environments. Overall, these technology-enhanced exergames challenge the adult user and modify the experience by increasing sensory stimulation and creating an environment where virtual and real elements interact. As a therapy, exergames can potentially create new environments and visualizations that may be more ecologically valid and thus simulate real activities of daily living that can be trained. Furthermore, by adding telemedicine features to the exergame, progress over time can be closely monitored and feedback provided, offering future opportunities for cognitive-motor assessment. To more optimally serve and challenge adults both physically and cognitively over time in future lockdowns, there is a need to provide long-term remote training and feedback. Particularly related to activities of daily living that create opportunities for effective and lasting rehabilitation for elderly and sufferers from chronic non-communicable diseases (CNDs). The aim of the current review is to envision the remote training and monitoring of physical and cognitive aspects for adults with limited mobility (due to disability, disease, or age), through the implementation of concurrent telehealth and exergame features using XR and wireless sensor technologies.